USING ONLINE SOCIAL NETWORKING SITES FOR DOING BUSINESS - A MARKETING RESEARCH - FUCIU, Mircea; DUMITRESCU, Luigi (Annales Universitatis Apulensis Series Oeconomica, 2014)
The developments of the information and communication technologies of the last decades (especially the Internet and the online social networks - OSN) have created a new environment for the development of new business opportunities or for the expansion of the older ones. Through these new changes, new challenges have arisen, faster communication, the need to be out there 24/7, a greater care of what you offer to the market. Our paper presents a small part of a marketing research (qualitative and quantitative) which aims to understand how the online social networking sites can be used by the companies for developing their businesses. We are presenting a short introduction a literature review in the field of OSN its evolution and its types followed by the research methodology and the research results. At the end of the paper we are presenting several conclusion of the research and how can the OSN be used for doing business.